Contralateral routing of signals disrupts monaural level and spectral cues to sound localisation on the horizontal plane - Pedley, Adam J.; Kitterick, Pádraig T. (Elsevier, 2017)
Objectives: Contra-lateral routing of signals (CROS) devices re-route sound between the deaf and hearing ears of unilaterally-deaf individuals. This rerouting would be expected to disrupt access to monaural level cues that can support monaural localisation in the horizontal plane. However, such a detrimental effect has not been confirmed by clinical studies of CROS use. The present study aimed to exercise strict experimental control over the availability of monaural cues to localisation in the horizontal plane and the fitting of the CROS device to assess whether signal routing can impair the ability to locate sources of sound and, if so, whether CROS selectively disrupts monaural level or spectral cues to horizontal location, or both.